Preparation and Properties of Three-Dimensional Ordered Macroporous Loaded Pt-SO42-/ZrO2 Solid Super Acid - Chang, Qiaowen; Yan, Caixin; Yu, Juan; Ye, Qingsong; Jiang, Jing; Chen, Jialin; Liu*, Weiping (Asian Journal of Chemistry, 2014)
Three-dimensional ordered macroporous SiO2 (3DOMS) was duplicated by using poly(methyl methacrylate) (PMMA) latex spheres as the template. Pt-SO42-/ZrO2 solid super acid supported on this macroporous structure material was prepared by impregnation-roasting method and characterized by using TEM, XRD and the N2 sorption capacity. The effect of ZrO2 content on the 3DOMS structure was explored. The results indicate that 3DOMS loaded with Pt-SO42-/ZrO2 exhibit ordered structure with strong acidity and high BET surface area, when the content for ZrO2 is optimized to 25 %. The macroporous solid superacid catalysts display high catalytic activity in liquid phase esterification reaction between acetic acid and n-butanol.